Faktor-Faktor Penghambat dalam Implementasi Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3): Systematic Literature Review - Daniel, Risyad Aldian; Fajar, Nur Alam; Windusari, Yuanita; Novrikasari, Novrikasari; Sunarsih, Elvi (Poltekkes Kemenkes Kendari, 2023)
Occupational safety and health (OSH) are an important health issue that requires attention, both from the government and business owners to their workers. One of the main causes of work accidents is the low awareness of the importance of implementing OHS in the workplace. SMK3 must be implemented for companies, especially companies that have a high risk of work accidents and have a workforce of more than 100 people. The method in this study uses a systematic review method of previous research results. The results showed that the Occupational Health Safety Management System (SMK3) is an important role in overcoming inhibiting factors and part of the management of a company that focuses on protecting occupational safety and health (K3) for workers. With the aim of increasing the effectiveness of OHS protection, preventing and minimizing the incidence of work accidents and occupational diseases, and creating a safe, comfortable and efficient workplace. However, in this case there are several factors that hinder the implementation of SMK3, including financing, weak law enforcement, lack of awareness from workers, and lack of education about occupational safety and health in the form of counseling, training or providing information in the form of pocket books or posters.